Key interface module and lock - WEI YIXING; ZHANG ZHOUHAI; FANG SICONG (2024)
The key interface module comprises a shell, a wireless chip and a dustproof assembly, the shell is provided with a key inserting hole for exposing a lock cylinder, the wireless chip is installed on the shell, and the dustproof assembly is movably installed on the shell and used for opening or closing the key inserting hole. And the key interface module is an integrated module assembly which can be mounted at the end part of the key interface of the lock cylinder. Through the arrangement, the key interface module has a dustproof function and an identity identification function at the same time, so that the lock has the identity identification function and the dustproof function only by installing the key interface module on the lock cylinder, the universality of the key interface module is improved, the development and production cost is reduced, and the overall production efficiency of the lock is improved; meanwhile, when the dustproof function or the identity recognition function of the lock is damaged, onl